(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the use of probiotics and prebiotics supplementation in autistic children. Methodology: Articles were identified in the PubMed and SciELO databases. In order to locate the studies, descriptors in English obtained from the Health Sciences Descriptors (DeCS), were used: Prebiotics. Probiotics. Autism Spectrum Disorder. Gut microbiota. Bifidobacterium. The search was limited to articles in Portuguese and English and comprised the years of publication between 2015-2021. Results: A total of 6 clinical trials conducted on children with autism have been systematically reviewed. Regarding the types of supplements used, there were 3 studies that used probiotics, 2 that used prebiotics and probiotics and 1 that made only the use of prebiotics. Despite the scarce amount of studies, they have had remarkable results in relation to the supplementation of probiotics and prebiotics in children with ASD. In some studies, it was possible to observe an improvement in the severity of autism and improvements in relation to antisocial behavior, while in others, there was an increase in beneficial bacteria and a decrease in pathogens in the gastrointestinal tract, leading to an improvement in recurrent gastrointestinal symptoms. Conclusion: The use of prebiotics and probiotics has shown significant results in children with ASD, being an alternative, promising and complementary therapy. Still, there is a need for more clinical trials to be carried out on the subject, as they are scarce and with small samples.